Reliable liquid chromatography‐mass spectrometry method for investigation of primary aromatic amines migration from food packaging and during industrial curing of multilayer plastic laminates†. (10th September 2014) - Lambertini, Francesca; Di Lallo, Valentina; Catellani, Dante; Mattarozzi, Monica; Careri, Maria; Suman, Michele; Giorgi, Gianluca
<x xml:space="preserve">Abstract</x> Primary aromatic amines (PAAs) can migrate from packaging into food from different sources such as polyurethanic adhesives used for the manufacture of multilayer films, which may contain residual aromatic isocyanates, or recycled paperboard, because of the presence of azo dyes in the printed paper massively used in the recycling process. In the present work, a reliable analytical method, exploiting a conventional high‐performance liquid chromatography‐(selected ion monitoring)‐mass spectrometry system, for PAAs compliance assessment in food contact materials was developed as an effective alternative to the current standard spectrophotometric one, moving in this way from the screening to the accurate and selective quantitation perspective for the analysis of PAAs both in aqueous and acidic food simulants. The main validation parameters were verified achieving very satisfactory results in terms of linearity range, limit of detection (ranging from 0.1 to 1.0 µg kg−1) and quantitation (ranging from 0.1 to 3.6 µg kg−1), repeatability and accuracy. Suitability of the method was demonstrated for a wide range of commercial samples, chosen among different producers of the most common used food packaging plastic and paperboard categories and then analyzed to assess the risk related to PAAs migration. Finally, the method was also successfully exploited to monitor the evolution of potential PAAs migration during the industrial curing process of multilayer plastic laminates, prior to their release for delivery to the food industry end user. Copyright © 2014 John Wiley & Sons, Ltd.